Metal Binding Ability of Microbial Natural Metal Chelators and Potential Applications - Retamal-Morales, G (Royal Society of Chemistry, 2020)
Siderophores are natural products which have attracted interest due to their ability to bind metal ions with high affinities. This review considers the complex formation of these natural chelators with all kinds of different metal and metalloid ions and links their chelating properties to potential biotechnological applications and towards environmental context. © 2020 The Royal Society of Chemistry.